Transient expression of interleukin-7 in nicotiana benthamiana using agro-infiltration - Hoang, Nguyen Huy; Ngoc, Pham Bich; Son, Le Van; Ha, Chu Hoang (Academia Journal of Biology, 2017)
Interleukin-7 (IL-7) is a cytokine that plays an important role in promoting growth and development of CD4 and CD8 immune cells in humans. IL-7 is also a target of the attack of some invasive pathogens. In this study, IL-7- coding gene was cloned into pRTRA vector to generate a cassette 35S-IL7-cmyc-histag-100xELP, and then this cassette was inserted into a binary vector pCB301. This construct was transformed into Nicotiana benthamiana using agro-infiltration for transient expression assay. Western blot was used to confirm expression of IL-7 in N. benthamiana on the 5th day of post-agro-infiltration. The results show that there were two bigger size of IL-7 with molecular weights of 64 and 130 KDa resulted from post translational modification. IL-7 was purificated from 1 kg of fresh tobacco leaves with the quantity of 3.15% of total soluble protein using immobilized metal ion chromatography method and evaluated by the Image J software. These results set forward the stage of studies on the safety and therapeutic applications of plant-derived recombinant IL-7 protein to humans. Citation: Nguyen Huy Hoang, Pham Bich Ngoc, Le Van Son, Chu Hoang Ha, 2017. Transient expression of a taste-modifying protein, interleukin-7, in nicotiana benthamiana using agro-infiltration. Tap chi Sinh hoc, 39(2): 232-238. DOI: 10.15625/0866-7160/v39n2.9000. *Corresponding author: chuhoangha@ibt.ac.vn Received 13 December 2016, accepted 20 May 2017